Catalytic co-pyrolysis of red cedar with methane to produce upgraded bio-oil. (August 2019) - Tshikesho, Redemptus S.; Kumar, Ajay; Huhnke, Raymond L.; Apblett, Allen
Highlights: Biomass was co-pyrolyzed with methane over molybdenum modified and base HZSM-5. Incorporation of methane over MoZn/HZSM-5 improved bio-oil properties. Bio-oil yield was the highest with methane over MoZn/HZSM-5 at 650 °C. Aromatics hydrocarbons yield was the highest with methane over MoZn/HZSM-5 at 750 °C. Abstract: Fast pyrolysis is a promising route to transform biomass into bio-oil for further refining into transportation fuels and chemicals. However, bio-oil applications suffer from several challenges due to its adverse properties. This study reports improving bio-oil properties through co-pyrolysis of biomass with methane over molybdenum/zinc (MoZn/ZHSM-5) and HZSM-5 catalysts that promote deoxygenation, decarbonylation, hydrogen transfer and aromatization reactions. The co-pyrolysis was conducted at 650 °C and 750 °C in a micro-scale reactor and a bench-scale reactor. The highest bio-oil yield, energy content, and energy yield of 53.4%, 10.2 MJ/kg, and 29.9%, respectively, were obtained with methane over MoZn/HZSM-5 at 650 °C. Acids, alcohols, aldehydes, benzene derivatives, BTEXs, furans, ketones, PAHs, and phenols were detected in bio-oils while phenols dominated under most conditions. Oxygenated compounds decreased using MoZn/HZSM-5 with methane at 750 °C. The results demonstrate that methane used with catalysts can reduce oxygenated compounds and improve properties and yield of bio-oil.